2018
DOI: 10.5505/kpd.2018.70783
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Aggression and Restriction Methods in Psychiatric Settings of a Training and Research Hospital

Abstract: Objective: Aggression is a significant problem seen in psychiatric clinics, which can cause physical and psychological trauma. The aim of this study is to investigate aggression and restriction methods in psychiatric settings of a training and research hospital. Method: This descriptive study was conducted in psychiatry services and the Alcohol and Substance Addiction Research Treatment and Education Center between April 1, 2014 and March 31, 2015. The data were collected retrospectively reviewing the complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“… 20 The distribution of diagnoses is also similar to another study from a mental hospital in Istanbul, with a lower rate of emergency hospitalizations at our hospital. 21 A study from another training hospital in Turkey has also found no significant difference with regard to the working hours, 3 which might be related to the general lower rate of admissions during night shifts. Yet, findings from other studies indicate that restraint measures are more often resorted to during night shifts.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 20 The distribution of diagnoses is also similar to another study from a mental hospital in Istanbul, with a lower rate of emergency hospitalizations at our hospital. 21 A study from another training hospital in Turkey has also found no significant difference with regard to the working hours, 3 which might be related to the general lower rate of admissions during night shifts. Yet, findings from other studies indicate that restraint measures are more often resorted to during night shifts.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, findings from other studies indicate that restraint measures are more often resorted to during night shifts. 3 , 8 , 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiziksel kısıtlama oranına ilişkin bulgular, Türkiye'de yapılan diğer tek merkezli çalışmalardaki sonuçlar ile uyumludur (5,8,9). Fiziksel kısıtlama süresine ilişkin bulgular, farklı ruh sağlığı kliniklerinde yapılan fiziksel kısıtlama uygulamaları ile karşılaştırıldığında görece olumlu olmakla beraber (2,17,18), ruh sağlığı dal merkezi acil servisi olması itibariyle yataklı servislere göre daha kısa süre fiziksel kısıtlama yapılması beklenebilir bir olgu olarak değerlendirilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Bu terim, onam alınmadan yapılan tedavi uygulamaları (involuntary treatment/treatment without consent), tecrit (isolation) ya da hastanın fiziksel hareketini engelleyecek şekilde kısıtlamaları (restraint) kapsamaktadır. Kısıtlama elle, mekanik veya kimyasal (psikotrop ilaçların tedavi amacı dışında hareketi kısıtlamaya yönelik kullanılması) tipte olabilir (1)(2)(3)(4).…”
Section: Introductionunclassified